2015
DOI: 10.1111/aab.12240
|View full text |Cite
|
Sign up to set email alerts
|

The importance of water potential range tolerance as a limiting factor onTrichodermaspp. biocontrol ofSclerotinia sclerotiorum

Abstract: Biological control of fungal phytopathogens is often more variable in efficacy compared with disease suppression achieved by conventional pesticide use. Matching the environmental range of a potential biocontrol agent with that of the target phytopathogen is necessary if consistent disease suppression is to be achieved under field conditions. Strains of Trichoderma that could parasitise sclerotia of Sclerotinia sclerotiorum had their spore germination and mycelial growth (five strains) and ability to parasitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Environmental factors such as humidity, pH and temperature effects the endophytic interaction of fungi (Cook & Baker, 1983). For example, Trichoderma activity is influenced by soil moisture (Jones & Bienkowski, 2015), and Candida activity is effected atmospheric conditions add strength against apple pathogen (Usall et al, 2000). In a trial, variations were observed in the endophytic activity against Dutch elm disease, indicating that there may be some abiotic factors involved that influences endophytic activity .…”
Section: Dependencymentioning
confidence: 99%
“…Environmental factors such as humidity, pH and temperature effects the endophytic interaction of fungi (Cook & Baker, 1983). For example, Trichoderma activity is influenced by soil moisture (Jones & Bienkowski, 2015), and Candida activity is effected atmospheric conditions add strength against apple pathogen (Usall et al, 2000). In a trial, variations were observed in the endophytic activity against Dutch elm disease, indicating that there may be some abiotic factors involved that influences endophytic activity .…”
Section: Dependencymentioning
confidence: 99%
“…Some microorganisms act as phytopathogen controllers. This is the case for species of the genus Trichoderma, which parasitize and successfully control Sclerotinia [228,229], Fusarium [230], Verticillium [231], and Macrophomina [232] fungal species, among others, and show nematicidal activity against gall-forming Meloidogyne species [233][234][235]. In addition, the evaluation of functional traits of mycorrhizal, rhizospheric, or endophytic species has identified species with high potential to promote plant growth.…”
Section: Why Should We Know About Microbial Diversity?mentioning
confidence: 99%
“…Trichoderma spp. parasitize and successfully control phytopathogenic fungal species such as Sclerotinia (Jones et al, 2014, 2016), Fusarium (Saravanakumar et al, 2016), Verticillium (Carrero-Carrón et al, 2016), and Macrophomina (Khaledi and Taheri, 2016), among others, and have nematicidal effect on the gall-forming Meloidogyne (Sahebani and Hadavi, 2008; Feyisa et al, 2016; Sokhandani et al, 2016). This functional characteristic of Trichoderma and other biocontrol species responds to the increasing call for practices that minimize the side effects left by pesticides, such as resistance in pest populations, reduction of soil and water quality, and the generation of residues with harmful effects on non-target organisms.…”
Section: Agricultural Technological Microbiologymentioning
confidence: 99%